Evaluation of the Relevance of a Web-Based "Ask an Expert" Feature: StratSoy and Soy and Human Health Queries - D. L. Wood; A. G. Kanfer; J. Michaels; S. Thompson; S. A. Morris; C. M. Hasler (Journal of Applied Communications, 2000)
StratSoy, a state-of-the-art Web-based information system, has an "Ask an Expert" (AE) feature that allows Web site browsers to question experts in 13 areas including Soy and Human Health (SHH). The objectives of this research were to: a) assess the use of the SHH AE feature; b) examine respondent attitudes about soy-related topics to help guide development of a Frequently Asked Questions (FAQ) section; and c) improve the information dissemination process on the Web site based on the results of this research. Study participants were 50 Web site users and 48 people who were unfamiliar with the site. The results of the study indicated topic areas of interest and additional Web site features desired by the respondents. The findings identified specific areas that may be targeted to improve the Web site.